2005
DOI: 10.1172/jci200523409
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurements document the dynamic cellular kinetics of chronic lymphocytic leukemia B cells

Abstract: Due to its relatively slow clinical progression, B cell chronic lymphocytic leukemia (B-CLL) is classically described as a disease of accumulation rather than proliferation. However, evidence for various forms of clonal evolution suggests that B-CLL clones may be more dynamic than previously assumed. We used a nonradioactive, stable isotopic labeling method to measure B-CLL cell kinetics in vivo. Nineteen patients drank an aliquot of deuterated water ( 2 H 2 O) daily for 84 days, and 2 H incorporation into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
308
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(331 citation statements)
references
References 22 publications
20
308
0
3
Order By: Relevance
“…In a small subset of CLL patients, the disease has a rapid course and requires early treatment. The dynamic cell turnover reported by recent studies (Messmer et al, 2005;van Gent et al, 2008) may well be linked with cell division rates, as well as with the period leukemic cells that reside in LN proliferation centers. Our findings indicate that modeling of the LN characteristics of CLL is feasible and can provide novel information on distinct responses in vitro to cytostatic drugs among prognostic subgroups.…”
Section: Discussionmentioning
confidence: 94%
“…In a small subset of CLL patients, the disease has a rapid course and requires early treatment. The dynamic cell turnover reported by recent studies (Messmer et al, 2005;van Gent et al, 2008) may well be linked with cell division rates, as well as with the period leukemic cells that reside in LN proliferation centers. Our findings indicate that modeling of the LN characteristics of CLL is feasible and can provide novel information on distinct responses in vitro to cytostatic drugs among prognostic subgroups.…”
Section: Discussionmentioning
confidence: 94%
“…7 While their majority in the peripheral blood is cell cycle arrested, CLL cells in lymphoid organs proliferate, delivering substantial amounts of tumor cells daily. 8 Critically, CLL cells in lymphoid niches are protected against cytotoxic effects of many chemotherapeutics and likely cause minimal residual disease and future relapse. 6 If leukemic cell proliferation is driven by K þ efflux, selective K þ channel blockers could be of clinical benefit to attack B cell neoplasms.…”
Section: Openmentioning
confidence: 99%
“…However, in vivo studies of tumor kinetics, using deuterated water, revealed higher than expected tumor cell turnover, with a birth rate of up to 2% per day. 2 The proliferative component of CLL appears to be confined to pseudofollicles or proliferation centers in secondary lymphoid tissues, 3,4 where interactions with non-neoplastic T cells 5,6 and follicular dendritic cells 7 take place, and promote tumor cell growth. 4 In contrast, very few CLL cells in the peripheral circulation show features of proliferation and those that do are believed to represent recent emigrants from the LN.…”
Section: Introductionmentioning
confidence: 99%